2018
DOI: 10.1104/pp.18.00709
|View full text |Cite
|
Sign up to set email alerts
|

The Patterned Structure of Galactoglucomannan Suggests It May Bind to Cellulose in Seed Mucilage

Abstract: The interaction between mannan polysaccharides and cellulose microfibrils contributes to cell wall properties in some vascular plants, but the molecular arrangement of mannan in the cell wall and the nature of the molecular bonding between mannan and cellulose remain unknown. Previous studies have shown that mannan is important in maintaining Arabidopsis () seed mucilage architecture, and that Cellulose Synthase-Like A2 (CSLA2) synthesizes a glucomannan backbone, which Mannan α-Galactosyl Transferase1 (MAGT1/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 69 publications
2
88
1
Order By: Relevance
“…The presence of regular substitution patterns in wood mannans remains elusive 36 , although a recent study evidences that both xylans and mannans are intimately bound to cellulose surfaces in a semi-crystalline fashion in spruce wood 57 . It seems that an even placement of glucose and mannose units in the backbone of glucomannans benefits the interaction with cellulose surfaces 37,58 , and preliminary evidence of the occurrence of such motifs in spruce glucomannan has been recently reported 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of regular substitution patterns in wood mannans remains elusive 36 , although a recent study evidences that both xylans and mannans are intimately bound to cellulose surfaces in a semi-crystalline fashion in spruce wood 57 . It seems that an even placement of glucose and mannose units in the backbone of glucomannans benefits the interaction with cellulose surfaces 37,58 , and preliminary evidence of the occurrence of such motifs in spruce glucomannan has been recently reported 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type of biomass and pretreatment technology, pretreated biomass contains, in addition to cellulose, varying amounts of linear and branched polysaccharides, including the hemicelluloses xylan, glucomannan and xyloglucan, as well as pectin, all of which adhere to cellulose fibers, forming a complex three-dimensional matrix [323]. These polysaccharides can form multiple substructures, and while many hemicelluloses are relatively easy to degrade, a fraction of these polysaccharides will form recalcitrant co-polymeric substructures that may hamper cellulose degradation [47,261,392]. Due to the high complexity of these plant polysaccharides, a variety of enzyme activities are needed for their complete breakdown ( Table 1).…”
Section: Hemicellulolytic Enzymesmentioning
confidence: 99%
“…It has been shown that galactoglucomannan from the primary cell walls of ripe kiwifruit contains mannose, glucose and galactose in the molar ratio 2 : 2 : 1 (Schr€ oder et al, 2001). Galactoglucomannan with a similar molar ratio of mannose, glucose and galactose was also found in Arabidopsis seed mucilage (Voiniciuc et al, 2015;Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%